Coexistence of SC and AFM in two-orbital model for s±-wave iron based superconductors. (June 2019) - Pradhan, B.; Parida, P.K.; Sahoo, S.
Abstract: The gap structure and pairing mechanism for iron based superconductors is hotly discussed as a central issue since their discovery. The long range order parameters, electronic specific heat, conduction electron density of states and energy band structure of iron based superconductors are calculated by a tight-binding two-orbital model with the coexistence of superconductivity and antiferromagnetism. We have proposed here a s ± -wave pairing symmetry of the form cos k x  × cos k y in a two-orbital model for the coexistence of the two order parameters in the mean-field approximation. The model is solved by Zubarev's double-time Green's function technique to find their self-consistent gap equations and are solved self-consistently numerically. Highlights: A Hamiltonian for Fe based SCs with SC and AFM interactions is proposed. Zubarev's technique of single particle double time Green's functions is used for calculations. The interplay of the gap parameters are studied and the gap values are observed through DOS plots. . Specific heat jumps are observed at the transition temperatures. Band energies are also studied.